Multiple Realities and Hybrid Objects: A Creative Approach of Schizophrenic Delusion - Cermolacce, Michel; Despax, Katherine; Richieri, Raphaëlle; Naudin, Jean (Frontiers in Psychology, 2018)
Delusion is usually considered in DSM 5 as a false belief based on incorrect inference about external reality, but the issue of delusion raises crucial concerns, especially that of a possible (or absent) continuity between delusional and normal experiences, and the understanding of delusional experience. In the present study, we first aim to consider delusion from a perspectivist angle, according to the Multiple Reality Theory. In this model inherited from Alfred Schültz and recently ad-dressed by Gallagher, we are not confronting one reality only, but several (such as the reality of everyday life, of imaginary life, of work, of delusion, etc.). In other terms, the Multiple Reality Theory states that our own experience is not drawing its meaning from one reality identified as the outer reality but rather from a multiplicity of realities, each with their own logic and style. Two clinical cases illustrate how the Multiple Realities Theory may help address the reality of delusion. Everyday reality and the reality of delusion may be articulated under a few condi-tions, such as compossibility (i.e. Double Book-Keeping, in Bleulerian terms) or flexibility. There are indeed possible bridges between them. Possible links with neuroscience or psychoa-nalysis are evoked. As the subject is confronting different realities, so do the objects among and towards which a subject is evolving. We call such objects Hybrid Objects due to their multiple belonging. They can operate as shifters, i.e. as some functional operators letting one switch from one reality to another. In the final section, we will emphasise how delusion flexibility, as a dynamic interaction be-tween Multiple Realities, may offer psychotherapeutic possibilities within some reality shared with others, entailing relocation of the present subjects in regained access to some flexibility via Multiple Realities and perspectivism.